Towards an Indigenous-Serving Institution: A Study on Sense of Belonging and Perceptions of Native Hawaiian Culture at Leeward Community College - T. Kuʻuipo Cummings Losch (Journal Committed to Social Change on Race and Ethnicity, 2024)
Leeward Community College is committed to supporting Native Hawaiians, the Indigenous people of Hawaiʻi. It aims to become a “model indigenous-serving” institution (University of Hawaiʻi, 2012) as part of the University of Hawaiʻi system’s efforts to empower Hawaiʻi’s Indigenous scholars and their communities. This single-site case study used the Culturally Engaging Campus Environments (CECE) model to assess the degree to which students feel a sense of belonging on their college campus, specifically in their perceptions of Native Hawaiians and Native Hawaiian culture. The data revealed that while most participants felt a sense of belonging on campus, there are disparities between Native Hawaiian and non-Native Hawaiian students and employees. Interviewees emphasized the need for institutional support to prioritize indigenous people, mindsets, environments, and collective wellness in decision-making, leadership, and service to the community.